EFFECTIVENESS OF COMBINED THORACIC EPIDURAL AND LIGHT GENERAL ANAESTHESIA IN PATIENTS UNDERGOING NON-CARDIAC THORACIC SURGERY - Nasir, Khawaja Kamal; Mansoor, Faraz; Khan, Imran Mohammad; Zafar, Ayaz -bin-; Ali, Safdar; Ahmad, Jawad (Journal of Ayub Medical College Abbottabad, 2004)
Background: The specialty of thoracic anaesthesia has emerged as a scientifically based discipline just 30 years back. At the start of the 20th century empyema and tuberculosis were the main indications for the thoracic surgery. Later on with the introduction of antibiotics lung malignancies were more commonly operated. Recent resurgence of tuberculosis and associated medical illnesses put these patients in high risk for surgery and anaesthesia, necessitating introduction of more skilful approach. The objective of this study was to evaluate the effectiveness of combined thoracic epidural anaesthesia and light general anaesthesia in patients undergoing non-cardiac thoracic surgery. Methods: This study was conducted at the department of Anesthesia and Intensive care, Pakistan Institute of Medical Sciences, Islamabad from 1st Jan 2001 to 31st August 2002. Ten adult patients of both sexes of ASA grade I-III, < 68 years of age, who were undergoing non-cardiac thoracic surgery were included. Thoracic epidural and central venous lines were placed 20 to 30 minutes before the start of procedure. All patients received same premedication, induction agents, analgesics, inhalational agents and muscle relaxants. All patients were transferred to Surgical Intensive Care unit after completion of the procedure. Results: Seventy percent patients were operated on lungs, twenty percent on mediastinum and one percent for carcinoma of esophagus. Only one patient had co morbid disease of hypertension. One patient (10%) died of massive intraoperative hemorrhage. One patient (10%) developed superior vena caval obstruction, that was to be operated for mediastinal growth. Rest of eight (80%) patients were extubated in the operation theatre. All (100%) patients received intraoperative blood transfusion. 20 % patients' required additional analgesia in the postoperative period. 20% developed postoperative arrhythmias. Conclusion: Combined use of light general anaesthesia and thoracic epidural is effective in patients undergoing non-cardiac thoracic surgery. Key Words: Non-cardiac thoracic surgery. Thoracic epidural. Epidural tramadol.